2011
DOI: 10.1111/j.1600-0536.2010.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

The EU Nickel Directive revisited-future steps towards better protection against nickel allergy

Abstract: In July 2001, the EU Nickel Directive came into full force to protect European citizens against nickel allergy and dermatitis. Prior to this intervention, Northern European governments had already begun to regulate consumer nickel exposure. According to part 2 of the EU Nickel Directive and the Danish nickel regulation, consumer items intended to be in direct and prolonged contact with the skin were not allowed to release more than 0.5 µg nickel/cm2/week. It was considered unlikely that nickel allergy would di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 42 publications
1
74
0
3
Order By: Relevance
“…15,[21][22][23] No entanto, a aplicação destas medidas preventivas tem exercido efeitos positivos na sensibilização, reduzindo significativamente a percentagem da população sensibilizada ao Ni, sobretudo nos países nórdicos, pioneiros nesta iniciativa. 14,15,24 Comprovando o interesse destas medidas verifica-se que a sensibilização ao Ni na Dinamarca é significativamente inferior nas mulheres jovens cujas orelhas foram furadas depois da implementação destas medidas que regulamentam a quantidade de níquel libertada pelos adornos metálicos (odds ratio 1,20 vs 3,34).…”
Section: -1996unclassified
See 1 more Smart Citation
“…15,[21][22][23] No entanto, a aplicação destas medidas preventivas tem exercido efeitos positivos na sensibilização, reduzindo significativamente a percentagem da população sensibilizada ao Ni, sobretudo nos países nórdicos, pioneiros nesta iniciativa. 14,15,24 Comprovando o interesse destas medidas verifica-se que a sensibilização ao Ni na Dinamarca é significativamente inferior nas mulheres jovens cujas orelhas foram furadas depois da implementação destas medidas que regulamentam a quantidade de níquel libertada pelos adornos metálicos (odds ratio 1,20 vs 3,34).…”
Section: -1996unclassified
“…13 Desde a introdução destas Directivas comunitárias, nos países nórdicos tem havido uma diminuição da sensibilização aos metais. 14,15 A aplicabilidade destas medidas e o seu grau de impacto permanece por avaliar em Portugal.…”
unclassified
“…jewellery often results in skin sensitization and dermatitis at the site of skin contact. Several field studies have recently demonstrated that nickel release in concentrations that result in sensitization and dermatitis remains common in Europe and the United States (Thyssen and Menne 2010;Thyssen et al 2011b). …”
Section: Metal Exposurementioning
confidence: 99%
“…The proportion of positive patch test reactions to nickel sulfate has remained stable at 10%-20% among young female German dermatitis patients (< 18 years) since the beginning of the new millennium (Schnuch et al, 2011 (Uter et al, 2009). There may be several explanations for this finding (Thyssen et al, 2011), but it is generally accepted that excessive nickel release from consumer items is one of the most important single factors (Schnuch & Uter, 2003).…”
Section: Nickelmentioning
confidence: 99%